2017
DOI: 10.1590/1516-3180.2016.0252150217
|View full text |Cite
|
Sign up to set email alerts
|

Complex karyotype including ring chromosome 11 in a patient with acute myeloid leukemia: case report

Abstract: CONTEXT: Complex karyotypes in acute myeloid leukemia (AML) are characterized by an overall low response rate with frequent relapses after clinical treatment. CASE REPORT: Here, we describe the case of a 61-year-old obese female with clinically diagnosed AML who presented a complex karyotype involving an uncommon abnormality: ring chromosome 11. Immunophenotypic analysis confirmed the diagnosis. Classical and molecular cytogenetic analyses, using GTG banding and FISH (fluorescence in situ hybridization), revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Interestingly, we identified chromosomal alterations in AT samples that represent the hallmark of topoisomerase inhibitors, such as Adriamycin (Salas et al, ; Meyer et al, ; Piredda et al, ), like alterations in 17q21, and the 11q23 rearrangements, which were observed multiple times in the AT sample of ABVD‐122. The 11q23 breakpoint is prone to form chromosomal rearrangements and may lead to gene fusion that could immortalize an early progenitor cell, having both lymphoid or myeloid potential (De Braekeleer et al, ; Ornellas et al, ). Deletions in chromosomes 7 and 5 or 17q21 abnormalities were also observed in three out of five patients; these alterations have been previously related to acute myeloblastic leukemia and acute lymphoblastic leukemia or mixed lineage (biphenotypic) leukemia (MLL) (Salas et al, ; Ornellas et al, ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we identified chromosomal alterations in AT samples that represent the hallmark of topoisomerase inhibitors, such as Adriamycin (Salas et al, ; Meyer et al, ; Piredda et al, ), like alterations in 17q21, and the 11q23 rearrangements, which were observed multiple times in the AT sample of ABVD‐122. The 11q23 breakpoint is prone to form chromosomal rearrangements and may lead to gene fusion that could immortalize an early progenitor cell, having both lymphoid or myeloid potential (De Braekeleer et al, ; Ornellas et al, ). Deletions in chromosomes 7 and 5 or 17q21 abnormalities were also observed in three out of five patients; these alterations have been previously related to acute myeloblastic leukemia and acute lymphoblastic leukemia or mixed lineage (biphenotypic) leukemia (MLL) (Salas et al, ; Ornellas et al, ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The 11q23 breakpoint is prone to form chromosomal rearrangements and may lead to gene fusion that could immortalize an early progenitor cell, having both lymphoid or myeloid potential (De Braekeleer et al, ; Ornellas et al, ). Deletions in chromosomes 7 and 5 or 17q21 abnormalities were also observed in three out of five patients; these alterations have been previously related to acute myeloblastic leukemia and acute lymphoblastic leukemia or mixed lineage (biphenotypic) leukemia (MLL) (Salas et al, ; Ornellas et al, ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic abnormalities involve either complete, partial loss, or gain of a chromosome; however, they play a significant role in the diagnostics, classification, prognostic value, and choice of therapy in AML [ 17 ]. The presence of very complex aberrations is associated with poor prognosis [ 17 , 18 ]. Many bodies of evidence have shown that TP53m are unique in functionality and form from the typical AML cases and have shown inconsistent responses to therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of very complex aberrations is associated with poor prognosis [ 17 , 18 ]. Many bodies of evidence have shown that TP53m are unique in functionality and form from the typical AML cases and have shown inconsistent responses to therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%